2020
DOI: 10.1038/s41596-020-0365-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined proximity labeling and affinity purification−mass spectrometry workflow for mapping and visualizing protein interaction networks

Abstract: Affinity purification coupled with mass spectrometry (AP-MS) and proximity-dependent biotinylation identification (BioID) methods have made substantial contributions to interaction proteomics studies. Whereas AP−MS results in the identification of proteins that are in a stable complex, BioID labels and identifies proteins that are in close proximity to the bait, resulting in overlapping yet distinct protein identifications. Integration of AP-MS and BioID data has been shown to comprehensively characterize a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 47 publications
(66 reference statements)
3
87
0
Order By: Relevance
“…3d). Using the BioID data and a previously described algorithm for mapping of protein localization 23,24 , we confirmed that similarly to GRPEL1 and GRPEL2, NERCLIN localizes to the mitochondrial matrix ( Fig. 3e).…”
Section: Bioid Analysis Of Proximal Proteins Suggests Distinct Functisupporting
confidence: 71%
See 1 more Smart Citation
“…3d). Using the BioID data and a previously described algorithm for mapping of protein localization 23,24 , we confirmed that similarly to GRPEL1 and GRPEL2, NERCLIN localizes to the mitochondrial matrix ( Fig. 3e).…”
Section: Bioid Analysis Of Proximal Proteins Suggests Distinct Functisupporting
confidence: 71%
“…The mass spec analysis was done in technical duplicates. The mass spectrometry data were analyzed as previously described 20,24 .…”
Section: Bioid Analysismentioning
confidence: 99%
“…In addition, a comparison of the results with previous publications (Gordon et al , 2020a ; Zhang, Cruz‐cosme, et al , 2020 ; Lee et al , 2021 ) showed that in most cases there was no obvious difference observed in the subcellular localization of individual ORFs in several transfected cell lines (Dataset EV7 ). To further characterize the potential compartment specificity of viral ORFs, we employed our developed MS‐microscopy system (Liu et al , 2020 ), which uses a quantitative interactome profile to map the cellular distribution of the bait protein (Fig EV4A and Dataset EV7 ). This revealed two baits (NSP16 and ORF3a) that were associated with endosomes, five baits (S, E, ORF7b, ORF8, and ORF10) that showed an ER distribution (Fig EV4A ), and four baits (M, ORF6, ORF7a, and NSP10) that were related to the Golgi apparatus.…”
Section: Resultsmentioning
confidence: 99%
“…Creative approaches using the combined power of AP-MS and BioID have enabled diversion of relative spatial distances for proteins within a complex [101,122]. Liu et al introduced this principle using a MAC-tag (StrepIII-BirA*), enabling the integration of stoichiometric complexation information from AP-MS with the identification of transient or proximal interactions by BioID.…”
Section: Discussionmentioning
confidence: 99%